Four days; the historical record of the death of President Kennedy - United Press International; American heritage (New York : American Heritage Pub. Co., 1964)
The events from the moment of President Kennedy's assassination to his burial three days later.
Keywords: Kennedy, John F. -- 1917-1963 -- Assassination; Kennedy, John F. -- 1917-1963 -- Death and burial; Kennedy, John F. -- 1917-1963 -- Assassination; Kennedy, John F. -- 1917-1963 -- Death and burial